Análisis jurídico y doctrinario de la mediación en los juicios laborales en el Ecuador - Torres Iñiguez, Franklin Willan (2016)
The issue that gave rise to this work of legal research is important , because in the Article 474 of the Job Code the creation of the Court of Arbitration and Mediation provides and as is clear from the statute invoked , are two members employer and two members by the workers , taking the fifth vote the Job Inspector who chairs this Court , however, when it comes to public institutions , the Court would be made by majority vote , leaving defenseless workers , so I believe that the Chief Justice should be a designated a Center of Mediation and Arbitration authorized by the Judicial Council , with the aim of ensuring the impartiality of the Chief Justice and the solution to the conflict Mediator collective is guaranteed. In this context the main objective of this work is to reform the Job Code stipulating a new conformation of the Court of Conciliation and Arbitration for the negotiation and final signing of the Collective Agreement and which is chaired by a member appointed by the Council of the Judiciary Ombudsman ensure absolute impartiality. Finally this research takes its importance for touching, investigate and propose a solution for the rights of workers